BENTUK PERLNDUNGAN HAK ATAS TANAH MASYARAKAT DARI POTESI LIKUEDAKSI DALAM PERENCANAAN TATA RUANG DAN WILAYAH - Safwan Hangkiho (Jurnal Perspektif Hukum, 2026)
This study aims to examine the regulatory dimensions of mortgage rights over land as credit collateral in Law Number 4 of 1996, and to analyze the legal consequences and executorial powers if the encumbrance and registration processes are not carried out in accordance with applicable provisions. As a material security institution, mortgage rights are designed to provide certainty and legal protection for creditors through constitutive mechanisms, namely the existence of a principal agreement, the creation of a Deed of Granting of Mortgage Rights (APHT), and registration at the Land Office. However, in practice, various problems are still found, such as procedural deviations, administrative defects, confiscation related to land objects, and obstacles in implementing execution when the debtor is in default, which has the potential to create a position for the creditor as a holder of preferential rights. This condition shows the urgency to normatively examine the effectiveness of the provisions in the UUHT as a regulatory instrument, as well as to enforce the laws that arise if formal requirements are not met. This study uses a normative legal method with a regulatory, conceptualization, and case approach, is descriptive-analytical, and relies on secondary data obtained through literature review and analyzed qualitatively with deductive reasoning and a prescriptive approach. The results of the study indicate that mortgage rights only have validity and executorial power if all formal requirements for encumbrance and registration are met; if not, then the right loses its constitutive nature, so that the creditor does not obtain preferential rights or executorial power and his position changes to that of a concurrent creditor who must go through a judicial process to obtain debt repayment, which ultimately causes legal protection to be less than optimal.